Energy migration dynamics of fluorescent protein layers adsorbed on chemically modified gold surfaces - Hanis Mohd Yusoff (Sendai, Japan: Tohoku University, 2014)
Research involving protein adsorption at an interface has extended into many areas since protein adsorption may induce denaturation or structural changes. Knowing the nature of adsorbed protein is interesting in the area such as biomaterials and pharmacology. In this study, a fluorescent protein (FP) has been chosen as a model to understand protein behaviour when adsorbed on a surface.